INCREASING THE VALUE OF EFL WRITTEN ASSESSMENT AND EVALUATION IN BENINESE EDUCATIONAL SYSTEM - KOTTIN, Assogba Evariste; EGOUNLETI, Pédro Marius; ZOUNHIN TOBOULA, Coffi Martinien (My University, 2022)
Abstract: In the process of EFL teaching and learning, the assessment and evaluation of written production are students’ performance focus where learners are mainly the ones to undergo this one side knowledge checking which is not done in collaboration with these learners but rather imposed to them. The fundamental objective of this study is to point out the difference between assessment and evaluation, examine the opportunities of written assessment and evaluation in Beninese educational system, and make a decision for learners’ effective success in this language skill. In order to collect reliable and valid data, a questionnaire of six (6) maim items including some prompts has been administered face to face and through Whatsapp messages to twenty-three (23) EFL teachers of Beninese secondary schools, twelve (12) collected, eighty-seven (87) learners in Beninese secondary schools, eighty (80) collected, six (6) university lecturers, four (4) collected, and fifty-five (55) university students, fiftyfive (55) collected, without forgetting face to face and phone call interviews of four (4) questions conducted with thirteen (13) EFL qualified teachers and two (2) inspectors. The results obtained from this investigation have been transcribed, analysed, and globally reveal that assessment and evaluation are very important in a country’s educational system and occupies a primordial place in language teaching and learning especially in English as a foreign language in Beninese context. It is essential to suggest that EFL teachers should recognise more and increase the value of assessment and evaluation in Beninese secondary schools so as to encourage students to keep on rating the target language learning. Résumé : Dans le processus de l’enseignement et de l’apprentissage de la langue anglaise, l’estimation et l’évaluation d’une production écrite prennent surtout en considération la performance des apprenants où ceux-ci subissent ce contrôle de connaissance à face unique qui n’est nullement fait en collaboration avec ces apprenants mais plutôt imposé à eux. L’objectif principal de cette étude est de mettre en exergue la différence entre l’estimation et l’évaluation, examiner les opportunités de l’estimation et de l’évaluation écrites dans le système éducatif du Bénin, et prendre une décision pour le succès effectif dans cette compétence. Pour la collecte des données fiables et valides, un questionnaire à six (6) items principaux a été distribué face-à-face et à travers des messages par Whatsapp à vingt-trois (23) enseignants d’Anglais aux cours secondaires du Bénin, douze (12) collectés, quatre-vingt-sept (87) apprenants aux cours secondaires du Bénin, quatre-vingts (80) collectés, six (6) enseignants d’universités, quatre (4) collectés, et cinquante-cinq (55) étudiants, cinquante-cinq (55) collectés, sans oublier les interviews face-à-face et par appels téléphoniques de quatre (4) questions conduites avec treize (13) professeurs certifiés et inspecteurs d’Anglais. Les résultats obtenus à partir de cette investigation ont été transcrits, analysés et révèlent globalement que l’estimation et l’évaluation sont très importantes dans le système éducatif d’un pays et occupe une place primordiale dans l’enseignement et l’apprentissage de la langue, particulièrement l’Anglais, langue étrangère dans le contexte du Bénin. Il est nécessaire de suggérer que les enseignants d’Anglais reconnaissent davantage et accroissent la valeur de l’estimation et de l’évaluation aux cours secondaires du Bénin en vue d’encourager les apprenants à continuer de prendre en considération l’apprentissage de la langue cible.
Keywords: Keywords: Valorising; writing; assessment; evaluation; education.; Mots-clés: Valoriser; écrit; estimation; évaluation; éducation.